Influence of ethanol, acidity and chloride concentration on the corrosion resistance of AISI 316L stainless steel - Ferreira, Elivelton A. [UNESP] (2013)
The influence of ethanol, sulfuric acid and chloride on the corrosion resistance of 316L stainless steel was investigated by means of polarization curves and electrochemical impedance spectroscopy measurements. Over the studied range, the steel corrosion potential was independent of H2SO 4 and NaCl concentrations in aqueous solution. On the other hand, in solution containing 65 wt.% ethanol and 35 wt.% water, the corrosion potentials were higher than those obtained in aqueous solution. Besides, the steel corrosion potential was affected by the addition of H2SO4 and NaCl in solution. In solutions with and without ethanol, plus 0.35 wt.% NaCl, the presence of 1 wt.% H2SO4 inhibited the appearance of pitting corrosion. © 2013 Sociedade Brasileira de Química.